2011
DOI: 10.1002/hipo.20761
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic activation of hippocampal neural stem cells in aged dentate gyrus

Abstract: Adult hippocampal neurogenesis contributes to the hippocampal circuit's role in cognitive functioning. New neurons are generated from hippocampal neural stem cells (NSCs) throughout life, but their generation is substantially diminished in aged animals due to a decrease in NSC proliferation. Because acetylcholine (ACh) is an important neurotransmitter released in the hippocampus during learning and exercise that is known to decrease with aging, we investigated whether aged NSCs can respond to ACh. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 71 publications
4
82
0
3
Order By: Relevance
“…Acetylcholine neurotransmission appears to be deregulated with age and in Alzheimer's disease, conditions with reduction in both neurogenesis and cognitive capacity. Notably, pharmacological modulation of the cholinergic activity in aged or stressed animals promotes NSCs' proliferation and corrects cognitive alterations (Itou et al 2011;Veena et al 2011b). The dopaminergic system has been shown to affect proliferation and differentiation of neural progenitor cells during embryonic development and in both adult neurogenic zones.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Acetylcholine neurotransmission appears to be deregulated with age and in Alzheimer's disease, conditions with reduction in both neurogenesis and cognitive capacity. Notably, pharmacological modulation of the cholinergic activity in aged or stressed animals promotes NSCs' proliferation and corrects cognitive alterations (Itou et al 2011;Veena et al 2011b). The dopaminergic system has been shown to affect proliferation and differentiation of neural progenitor cells during embryonic development and in both adult neurogenic zones.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Selective lesioning of the cholinergic system in the basal forebrain reduces proliferation of neuronal progenitor cells (Ma et al, 2000;Zhou et al, 2004;Mohapel et al, 2005). In both young and aged mice, focal application of ACh induces rapid calcium responses in Type 1 and Type 2 cells, suggesting that endogenous ACh might regulate stem cell activity by acting directly on proliferating cells (Itou et al, 2011). As mentioned above,Type 1 cells give rise to Type 2 cells that lack dendritic and axonal processes but may have short plump horizontal processes of unknown function.…”
Section: Progenitor Cells Do Not Receive Glutamatergic Innervationmentioning
confidence: 92%
“…Itou et al have reported positive effects of exercise on neural stem cells in the hippocampus [21]. Exercise-induced activation of cholinergic neurons has been implicated as a stimulus for hippocampal neurogenesis derived from neural stem cells in the dentate gyrus of mice over the age of 2 years [21].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Itou et al have reported positive effects of exercise on neural stem cells in the hippocampus [21]. Exercise-induced activation of cholinergic neurons has been implicated as a stimulus for hippocampal neurogenesis derived from neural stem cells in the dentate gyrus of mice over the age of 2 years [21]. Others report that exercise-induced increases in the synthesis of dihydrotestosterone caused by mild treadmill running are responsible for increased neurogenesis of hippocampal neurons in adult rats [22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%